2013
DOI: 10.1080/15287394.2013.834855
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Iron Impurities in the Toxic Effects Exerted by Short Multiwalled Carbon Nanotubes (MWCNT) in Murine Alveolar Macrophages

Abstract: Lung toxicity mediated by multiwalled carbon nanotubes (MWCNT) has been widely demonstrated and recently associated with induction of carcinogenic asbestos-like effects, but the chemical features which drive this toxic effect have still not been well elucidated. The presence of metals as trace contaminants during MWCNT preparation, in particular iron (Fe) impurities, plays an important role in determining a different cellular response to MWCNT.Our goal was to clarify the mechanisms underlying MWCNT toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 49 publications
2
67
0
Order By: Relevance
“…Furthermore, other factors influence the toxicity effects of MWCNTs and have the potential to modulate their biological effects, such as their sizes, 25 lengths, 26 and contamination with metal catalysts. 27 Several data indicate that length is one of the most important determinants for toxicity of CNTs and it is unclear whether the length of MWCNTs affects the outcome of immunotoxicity, which is one of the concerns in our study. Therefore, there is an extreme need for a better understanding of the relationship between the different functionalizations of MWCNTs and immune system.…”
mentioning
confidence: 83%
“…Furthermore, other factors influence the toxicity effects of MWCNTs and have the potential to modulate their biological effects, such as their sizes, 25 lengths, 26 and contamination with metal catalysts. 27 Several data indicate that length is one of the most important determinants for toxicity of CNTs and it is unclear whether the length of MWCNTs affects the outcome of immunotoxicity, which is one of the concerns in our study. Therefore, there is an extreme need for a better understanding of the relationship between the different functionalizations of MWCNTs and immune system.…”
mentioning
confidence: 83%
“…If CNTs are to reach their full potential for biotechnological applications (Bianco et al, 2005), new and scalable methods that allow for accurate cyto and genotoxicity evaluations need to be developed and implemented. Further, such methods should also allow for real-time assessment, minimum false positives, risk analysis of a variety of concentrations of nanomaterial being used for exposure, as well as risk correlations based on the nanomaterial length (Sato et al, 2005), diameter (Nagai et al, 2011), aggregation (Wick et al, 2007), impurities content (Aldieri et al, 2013), and/or surface chemistry (Saxena et al, 2007), just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that MWCNTs-ox possess pro-inflammatory activity and are endocytosed by healthy cells, inducing lysosomal dysfunction and mitochondrial damage in both healthy and tumoral cells. [64][65][66] Conversely, N-MWCNTs-ox and MWCNTs-ox were more easily endocytosed by tumoral cells and were less toxic. 52 It is possible that these nanoparticles are better tolerated, leading to minor intracerebral inflammation and increase in survival.…”
Section: Discussionmentioning
confidence: 99%